2022
DOI: 10.4236/ojce.2022.122015
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Fine Clay Soils Stabilized with Sugarcane Molasses

Abstract: Sugar cane molasses has proved cohesive and excellent performance on soil aggregates (fine particles). However, the microstructure of consolidated soil by the molasses is not yet subjected to research. The analysis results of sample without molasses (0%) and consolidated samples at 8%, 12%, and 16% show that the molasses acts on the structure of clayey fine soil developing its microstructure of airy matrix type (sample without molasses (0%) to a microstructure of a qualified type, more solid. Consolidated samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…On the whole, these results suggest that the molasses appears as the best in the optimization of the formulations and, consequently, this one contributes better to the improvement of thermo-mechanical performances of stabilized small bricks. Besides, this is justified in research works of Malanda and al (2022), in the microstructural behavior, and in coherence with works by Lima and al (2012), [13] [20].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…On the whole, these results suggest that the molasses appears as the best in the optimization of the formulations and, consequently, this one contributes better to the improvement of thermo-mechanical performances of stabilized small bricks. Besides, this is justified in research works of Malanda and al (2022), in the microstructural behavior, and in coherence with works by Lima and al (2012), [13] [20].…”
Section: Discussionsupporting
confidence: 59%
“…The dyeing change of clays of stabilized small bricks reveals that there has probabily had an unexpected chemical reaction between the molasses and the clayey soil. This mechanical behavior can also be explained by the realized microstructural analysis [Malanda and al, 2022].  Resistance in compression of clay small bricks, stabilized with the cassava starch…”
Section: Mechanical Resistance To the Small Bricks' Compressionmentioning
confidence: 89%
“…From a microstructural point of view, we have also observed the presence of inter-aggregate pores (mesopores) in the various samples analyzed, which suggests an evolution of the open soil structure towards a dense granular matrix [4]. However, the aim of this study is to compare four statistical thickness models: the Carbon Black model, the Harkins and Jura model, the Hasley model and the Jaroniec et al model, in the case of clayey concrete stabilized with sugarcane molasses, in order to find the optimum model that best simulates the phenomenon.…”
Section: Introductionmentioning
confidence: 70%
“…This change compared to unsterilized clayey concrete leads us to believe that stabilization using molasses brings about modifications to the external surface of clayey concrete by occupying the pores [4]. Ngouallat Mfoutou (2020) reports that 53.10 8 molasses molecules occupy the accessible surface of clay concrete [3].…”
Section: Samples Stabilized With 16% Cane Molassesmentioning
confidence: 99%
“…Molasses is a by-product of sugar production and is produced worldwide [ 18 , 19 ]. Many studies have shown that molasses can effectively bond to particulate matter [ 19 , 20 , 21 ]. For example, Benk and Coban [ 22 ] showed that molasses can substitute cement as a binder material to produce lightweight and heat-insulating bricks.…”
Section: Introductionmentioning
confidence: 99%